Shell microstructures of the helcionelloid mollusc Anabarella australis from the lower Cambrian (Series 2) Xinji Formation of North China - Li, Luoyang; Zhang, Xingliang; Skovsted, Christian B.; Yun, Hao; Li, Guoxiang; Pan, Bing (Journal of Systematic Palaeontology, 2019)
Although various types of shell microstructures are documented from Cambrian molluscs, the precise organization and mineralogical composition of Terreneuvian molluscs are relatively unknown. Anabarella was one of the first helcionellid molluscs to appear in the Terreneuvian, with the genus surviving until the third epoch of the Cambrian. Here, shell microstructures of Anabarella australis have been studied based on new collections from the lower Cambrian (Series 2) Xinji Formation of the North China Block. Results show that A. australis has a laminar inner shell layer that consists of crossed foliated lamellar microstructure (CFL). Nacreous, crossed-lamellar and foliated aragonite microstructures previously documented in the older (Terreneuvian) species A. plana are here revised as preservational artefacts of the CFL layers. This complex skeletal organization of Anabarella suggests that mechanisms of molluscan biomineralization evolved very rapidly. Morphologically, specimens from the Chaijiawa section show a pattern of distinct 'pseudo-dimorphism' as external coatings are identical to Anabarella, while associated internal moulds are similar to the helcionelloid genus Planutenia. In contrast, internal moulds from the Shangzhangwan section show considerable morphological variation owing to preservational bias and show greater similarities to specimens from South Australia, Northeast Greenland and Germany. These observations demonstrate that the extensive morphological variation seen in the internal moulds of the cosmopolitan genus Anabarella are primarily preservational artefacts and are unlikely to represent the real intra- and interspecific variability of the animal. In these cases, Planutenia is here confirmed to be a subjective synonym of Anabarella.